L(ocus ?) xanctus in Curiga (Monesterio, Badajoz) - Armin U. Stylow (Pallas, 2010)
It results from a new examination of the CIL II 1040 inscription, carved on the pedestal of a statue of Caracalla found at Curiga (Monesterio, Badajoz), that the emendation proposed by Hubner according to which its last line would refer to the dedication of a hundred-pound silver statue is unwarranted and useless. Its original reading already allowed us to corroborate the reading xancto in the last line and interpret it as a variant of sancto. The statue was therefore erected l(oco ?) sancto, at a place which was presumably situated at the centre of the antique municipum, but whose location remains unknown.